2006
DOI: 10.1016/j.aca.2006.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heavy metals in road-deposited sediments

Abstract: Road-deposited sediments were analysed for heavy metal concentrations at three different landuses (residential, industrial, commercial) in Queensland State, Australia.The sediments were collected using a domestic vacuum cleaner which was proven to be highly efficient in collecting sub-micron particles. Five particle sizes were analysed separately for eight heavy metal elements (Zn, Fe, Pb, Cd, Cu, Cr, Al and Mn). At all sites, the maximum concentration of the heavy metals occurred in the 0.45-75 m particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(87 citation statements)
references
References 24 publications
3
82
1
1
Order By: Relevance
“…In contrast, for a similarly sized university parking lot, Kayhanian et al (2012) found that only around 5% of the collected particulate mass was less than 38 µm in diameter. There is, however, agreement on particle numbers with car park surface dusts containing predominantly fine particles with reports of 97% being less than 38 µm (Kayhanian et al, 2012) or over 90% being below 150 µm (Herngren et al, 2006). Since street sweeping practices only efficiently remove coarser particles (German and Svensson, 2002), the problems posed by the finer, more contaminated particles will remain a significant problem in runoff where they tend to dominate on a mass distribution basis (Kayhanian et al, 2012).…”
Section: Accumulation Of Particulates/solidsmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, for a similarly sized university parking lot, Kayhanian et al (2012) found that only around 5% of the collected particulate mass was less than 38 µm in diameter. There is, however, agreement on particle numbers with car park surface dusts containing predominantly fine particles with reports of 97% being less than 38 µm (Kayhanian et al, 2012) or over 90% being below 150 µm (Herngren et al, 2006). Since street sweeping practices only efficiently remove coarser particles (German and Svensson, 2002), the problems posed by the finer, more contaminated particles will remain a significant problem in runoff where they tend to dominate on a mass distribution basis (Kayhanian et al, 2012).…”
Section: Accumulation Of Particulates/solidsmentioning
confidence: 95%
“…In a separate review, Sorme (2003) The concentrations of a range of metals reported in road dusts from a supermarket car park and from urban areas with similar characteristics to car parks are presented in Table 2. The studies were conducted in the same geographical region but represent diverse ranges of metal concentrations deriving from similar land-use types with the results reported by Herngren et al (2006) being two to three orders of magnitude lower than those of Gunawardana et al (2012). There is no obvious explanation for these large variations although it is accepted that differing metal concentrations will occur in these environments due to factors such as traffic density, weather conditions and neighbouring land-use activities.…”
Section: Accumulation Of Particulates/solidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The input of PAHs from point sources has gradually decreased because of enhanced discharge control (Schneider et al, 2001), while the input of PAHs from urban stormwater runoff has increasingly been reported as one of the most frequent causes of surface water pollution (Brenner et al, 2002;Murakami et al, 2004). PAHs in stormwater runoff tend to partition onto solid particles (Li et al, 2006), and street dust particle in urban runoff act as a transport medium for PAHs (Brown and Peake, 2006;Herngren et al, 2006). PAHs in street dust have various origins: weathering of materials from street surfaces, automobile exhausts, tyre particles, and atmospherically deposited materials (Takada * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%